Abducens nerve paralysis following spinal anesthesia [Spinal anesteziyi takiben gelişen abdusens sinir paralizisi] - (:unkn) unknown (My University, 2013)
Among the complications of spinal anaesthesia, 6th cranial nerve palsy occurs rarely. There is a possibility of encountering nerve injury during subarachnoid injections due to a long extracranial course. The symptoms appear as a result of ocular muscle paralysis. These symptoms often begin after the 4th day and spontaneous recovery lasts for weeks to months. We present a case in which Nervous Abducens palsy occurred following spinal anaesthesia for double j ureteral catheter placement surgery.
Keywords: Abducens nerve; Complication; Diplopia; Double j stent; Spinal anaesthesia